2019
DOI: 10.1371/journal.pone.0221211
|View full text |Cite
|
Sign up to set email alerts
|

Hospital burden of pulmonary arterial hypertension in France

Abstract: Background & aimsPulmonary arterial hypertension is a severe disease associated with frequent hospitalisations. This retrospective analysis of the French medical information PMSI-MSO database aimed to describe incident cases of patients with pulmonary arterial hypertension hospitalised in France in 2013 and to document associated hospitalisation costs from the national health insurance perspective.MethodsCases of pulmonary arterial hypertension were identified using a diagnostic algorithm. All cases hospitalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…That a debilitating disease like PAH have high HCRU after diagnosis is neither surprising nor unknown, 9 , 10 , 11 , 12 , 15 , 16 , 17 however, the costs for society before diagnosis is less studied 10 , 17 , 31 , 32 and the magnitude of productivity loss has not been shown before. Hospitalizations as a substantial cost driver after the PAH diagnosis 10 , 11 , 15 , 16 , 17 was confirmed by the present study and, importantly, productivity loss was found to be equally costly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That a debilitating disease like PAH have high HCRU after diagnosis is neither surprising nor unknown, 9 , 10 , 11 , 12 , 15 , 16 , 17 however, the costs for society before diagnosis is less studied 10 , 17 , 31 , 32 and the magnitude of productivity loss has not been shown before. Hospitalizations as a substantial cost driver after the PAH diagnosis 10 , 11 , 15 , 16 , 17 was confirmed by the present study and, importantly, productivity loss was found to be equally costly.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 6 , 7 , 8 This, together with disease targeted medical treatment, makes the economic burden of PAH substantial. 9 , 10 , 11 , 12 Estimations of the societal economic burden of PAH vary due to differences in data sources, selection of subjects, and cost components as well as changes in available treatments and treatment strategies over time. 12 Studies investigating indirect costs of PAH before and after diagnosis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence, prevalence, and phenotype of PAH display differences between studies, registries, presumably related to the design, structure biases, ranging from 2 to 52 cases per million inhabitants [1,[26][27][28][29][30].…”
Section: Pulmonary Arterial Hypertension -mentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a rare disease characterized by progressive pulmonary vascular resistance, eventual right heart failure, and high mortality [1]. It is frequently associated with hospitalization, an event indicative of disease progression and decreased survival [2][3][4]. A study using the Registry to Evaluate Early and Long-term PAH Disease Management (REVEAL Registry) reported that nearly 60% of patients newly diagnosed with PAH (N = 862) were hospitalized over a 3-year time period, with over 50% of the hospitalizations being PAH-related [3].…”
Section: Introductionmentioning
confidence: 99%